Diagnostic Performance of Serum IgG4 Levels in Patients With IgG4-Related Disease. Issue 41 (October 2015) - Yu, Kuang-Hui; Chan, Tien-Ming; Tsai, Ping-Han; Chen, Ching-Hui; Chang, Pi-Yueh
Abstract : Abstract: The aim of this study is to study the clinical features and diagnostic performance of IgG4 in Chinese populations with IgG4-related diseases (IgG4-RDs). The medical records of 2901 adult subjects who underwent serum IgG4 level tests conducted between December 2007 and May 2014 were reviewed. Serum concentrations of IgG4 were measured in 2901 cases, including 161 (5.6%) patients with IgG4-RD and 2740 (94.4%) patients without IgG4-RD (non-IgG4-RD group). The mean age of the IgG4-RD patients was 58.4 ± 16.1 years (range: 21–87), and 48 (29.8%) were women. The mean serum IgG4 level was significantly much higher in IgG4-RD patients than in non-IgG4-RD (1062.6 vs 104.3 mg/dL, P  < 0.001) participants. For IgG4 >135 mg/dL, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratio (LR)+, and LR− were 86%, 77%, 18%, 99%, 3.70, and 0.19, respectively. When the upper limit of normal was doubled for an IgG4 >270 mg/dL, the corresponding data were 75%, 94%, 43%, 98%, 12.79, and 0.26, respectively. For IgG4 >405 mg/dL (tripling the upper limit of normal), the corresponding data were 62%, 98%, 68%, 98%, 37.00, and 0.39, respectively. When calculated according to the manufacturer's package insert cutoff (>201 mg/dL) for the diagnosis of IgG4-RD, the corresponding sensitivity, specificity, PPV, NPV, LR+, and LR− were 80%, 89%, 29%, 99%, 7.00, and 0.23, respectively. For IgG4 >402 mg/dL (>2× the upper limit of the normal range), the corresponding data were 62%, 98%, 68%, 98%, 36.21, and 0.39, respectively. For IgG4 >603 mg/dL (>3× the upper limit of the normal range), the corresponding data were 50%, 99%, 84%, 97%, 90.77 and 0.51, respectively. The optimal cutoff value of serum IgG4 (measured by nephelometry using a Siemens BN ProSpec instrument and Siemens reagent) for the diagnosis of IgG4-RD was 248 mg/dL, the sensitivity and specificity were 77.6% and 92.8%, respectively. The present study demonstrated that 2 or 3 times the upper limit of the manufacturer's reference range of the IgG4 level was a useful marker for the diagnosis of various types of IgG4-RD and the optimal cutoff level was 248 mg/dL.